As tecnologias digitais como instrumentos potencializadores no ensino de língua portuguesa para surdos - Sousa, Francisco Ebson Gomes (2018)
This dissertation focuses on the learning of Portuguese Language (LP) by the deaf through digital technologies. The objective of the research is to analyze how deaf students can be aided by digital technologies in the production of texts in LP, taking into account the point of view of the students about this phenomenon and the possible teaching strategies that can be used for the production of LP texts by deaf people using digital technologies. Thus, it specifically aims to recognize what deaf students think about LP learning by focusing on textual production and; to identify possible teaching strategies that can be used for textual production in LP by deaf students making use of digital technologies. The considerations in this work were based on the reflections within the Pedagogy of Multiliteracies proposed by the New London Group (1996) and Rojo (2012). The research was qualitative and objective, both exploratory and descriptive, in which a pedagogical workshop was held teaching LP and later follow through applications that allow social networking, as was the case of Whatsapp. The research universe comprised a public school in Mossoró - RN, which attends the specific modality of care for deaf students, and a total of 20 deaf students participated. The corpus was constituted with the answers of the questionnaires about their perspectives on the LP and the interactions in the interaction group within the whatsapp application. With results still incipient, I believe that the textual production in digital environments is a great aid tool in the process of acquisition and development of second language, being the case of LP for deaf people, since most deaf students already have a constant access to these environments, as is the case of social networking sites, which can be used for LP learning. I also propose some tools that can be used as resources in learning LP through textual production through digital technologies